Manifestasi Klinis dan Gambaran Pencitraan Struktural dan Fungsional Berbagai Subtipe Demensia - Valentina Tjandra Dewi; Anak Agung Ayu Putri Laksmidewi (Cermin Dunia Kedokteran, 2023)
Dementia causes impaired cognition, behavior, and daily functional activities with physical, mental, and psychosocial consequences for patients, families, and communities. However, dementia diagnosis is still challenging. Classification of dementia subtypes also requires structuraland functional imaging studies. The structural imaging needed to support Alzheimer’s dementia and vascular dementia diagnosis is brain magnetic resonance imaging (MRI), frontotemporal dementia diagnosis can be supported by brain MRI or functional imaging, while Lewy Body dementia diagnosis requires functional imaging and biomarkers findings.